2020
DOI: 10.1002/pd.5673
|View full text |Cite
|
Sign up to set email alerts
|

Maternity health care professionals' views and experiences of fetal genomic uncertainty: A review

Abstract: The field of prenatal screening and diagnosis for fetal anomalies has been marked by a rapid succession of technological advances, including most notably, chromosomal microarray analysis, and next generation sequencing. Despite the diagnostic advantages of these technologies, their incorporation into prenatal testing has created additional challenges of revealing genomic variants of unknown or uncertain significance, and secondary findings. While detailed posttest counseling about uncertain variants is best pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…These studies have been conducted in countries including the Netherlands, 12 United States of America (USA), 13–15 United Kingdom (UK), 16–18 Hong Kong 19 and Australia 20,21 . The findings have highlighted differences in opinions and practice both across and within countries, regarding the management of uncertain results 22 . This is not surprising given the lack of consensus from some of the most notable professional bodies in terms of specific guidance around the reporting of uncertain results 23–29 .…”
Section: Introductionmentioning
confidence: 99%
“…These studies have been conducted in countries including the Netherlands, 12 United States of America (USA), 13–15 United Kingdom (UK), 16–18 Hong Kong 19 and Australia 20,21 . The findings have highlighted differences in opinions and practice both across and within countries, regarding the management of uncertain results 22 . This is not surprising given the lack of consensus from some of the most notable professional bodies in terms of specific guidance around the reporting of uncertain results 23–29 .…”
Section: Introductionmentioning
confidence: 99%
“…The understanding and perception of the utility of genomic sequencing approaches among paediatricians, midwives and obstetricians is variable 8–10 . Given the rapidly evolving nature of the field, it is imperative that both families and clinicians have a good understanding of the purpose, strengths and limitations of different types of genomic tests so that these are appropriately integrated into clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…The understanding and perception of the utility of genomic sequencing approaches among paediatricians, midwives and obstetricians is variable. [8][9][10] Given the rapidly evolving nature of the field, it is imperative that both families and clinicians have a good understanding of the purpose, strengths and limitations of different types of genomic tests so that these are appropriately integrated into clinical care. Additionally, genomic testing should include ready access to clinical geneticists and genetic counsellors, not only in returning prenatal results, but also to support clinicians and families to optimise the investigation of suspected genetic disease in the antenatal and post-natal periods, including the reanalysis of existing genomic data as the clinical situation evolves.…”
Section: Whole Exome Sequencing (Wes)mentioning
confidence: 99%
“…The likelihood of getting a result is also topical given that diagnostic yield has been found to vary considerably depending on whether the fetus has isolated or multiple anomalies [3]. Regarding time taken to receive results, parents waiting for ES results following the identification of a fetal anomaly have found the period long and trying [7] and studies have shown that some HPs including genetic counsellors as well as maternity HPs are concerned about returning these types of results to their patients and desire further guidance in this area [47][48][49].…”
Section: Discussionmentioning
confidence: 99%